Planeación Financiera a la Empresa Reencauchadora El Oro de la Ciudad de Machala Provincia de El Oro, Periodo 2015-2020 - Armijos Torres, Nelly Fabiola (2016)
The present thesis work entitled "financial business planning REENCAUCHADORA the gold from the city of MACHALA, province of gold, period 2015 - 2020", was it made in order to contribute effectively to the owner manager of the company can optimize resources and have a vision of the possible investments which take place in the next few years to strengthen and achieve increased profitability for business growth. Objectives stressing the implementation of financial planning to take advantage of opportunities and financial resources, seeking better performance and financial security, process the report of financial planning with conclusions and recommendations to improve the relevant aspects, in order to thus make the relevant corrective measures. The methodology used to comply with the proposed objectives began with the collection of information such as: financial statements, major, RUC, statements by the Contour and owner of the company. Once information has been obtained is predicted the sales, purchases and expenses for the analyzed periods 2015-2020, continuing with the process of financial planning was carried out the programs of inputs and outputs of the cash for drawing up the budget for cash and the projection of the financial statements for periods. 5 For the results of the financial planning, developed using the method percentage of sales forecast, to help the company to plan its activities for long term. As main conclusions we can mention that the company does not perform financial planning , which does not permit projecting future activities; resource management likewise made no cash budgets , thus not exactly known for financing availability , requiring financial planning that would be very supportive of their economic and financial situation , through the right decisions .